Resistance Exercise and Whey Protein Supplementation Reduce Mechanical Allodynia and Spinal Microglia Activation After Acute Muscle Trauma in Rats - Rodrigues, Gusthavo; Moraes, Thamyris; Elisei, Lívia; Malta, Iago; dos Santos, Rafaela; Novaes, Rômulo; Lollo, Pablo; Galdino, Giovane (Frontiers in Pharmacology, 2021)
Muscle injury originated by direct trauma to the skeletal muscle is among the main musculoskeletal disorders. Non-pharmacological treatments have been effective in controlling muscle-injury-induced pain, but few studies have investigated this response. Thus, the present study aimed to evaluate the effect of a resistance exercise training protocol combined or not to whey protein supplementation on muscle pain. In addition, was investigated the involvement of spinal glial cells in this process. Wistar rats underwent to the muscle injury model induced by direct trauma to the gastrocnemius muscle; and the muscle allodynia was measured by digital von Frey algesimeter test. To evaluate the effect of resistance exercise training protocol and/or whey protein supplementation on muscle allodynia, the animals exercised three times a week for 14 days and received supplementation daily for 14 days, respectively. In addition, the involvement of spinal glial cells on the muscle-injury-induced allodynia, as well as the effect of resistance exercise training and/or whey protein supplementation on these cells also was investigated by western blot assay. The results demonstrated that resistance exercise training and whey protein supplementation, combined or alone, reduced the muscle-injury-induced allodynia. Furthermore, was found that spinal microglia and astrocytes are involved in the muscle injury, and resistance exercise training combined with whey protein supplementation inhibited spinal microglia activation. The results suggest that resistance exercise training and whey protein supplementation may represent effective non-pharmacological treatments to control pain in the muscle after injury induced by acute trauma.